Characterization of pathological remodeling in the chronic atrioventricular block cynomolgus monkey heart - Hiroko Izumi-Nakaseko; Kengo Sakamoto; Ai Goto; Ryuichi Kambayashi; Akio Matsumoto; Yoshinori Takei; Akira Takahara; Atsushi Sugiyama; Atsushi Sugiyama (Frontiers Media S.A., 2023)
We studied time course of pathological remodeling occurring in the cynomolgus monkey hearts against persistent atrioventricular block condition (n = 10). The atrioventricular block induced the ventricular and atrial dilation followed by the ventricular hypertrophy. Interstitial fibrosis in the ventricle was also observed along with gradual increases in the plasma angiotensin II and aldosterone concentrations. These adaptations were associated with the changes in gene expression profiling reflecting fibrosis and hypertrophy. Atrioventricular block reduced the ventricular rate and cardiac output, but the ejection fraction and stroke volume increased, whereas the cardiac output was gradually restored to its basal level. Systolic/diastolic blood pressure after the atrioventricular block was kept equal to or lower than that before the block, according with lack of increase in the plasma catecholamine levels. Chronic atrioventricular block gradually prolonged the QRS width and JT interval, leading to the QT interval prolongation in conscious state. 10 mg/kg of dl-sotalol hydrochloride induced torsade de pointes (TdP) in 6 out of 10 animals by 15 months. Animals showing longer QTcF under anesthesia after the atrioventricular block developed dl-sotalol-induced TdP earlier. No marked difference was observed in pharmacokinetics of dl-sotalol between 1 and 7 months after the atrioventricular block. Each TdP spontaneously terminated, reflecting a monkey's relatively small "effective size of the heart (=∛(left ventricular weight)/wavelength of reentry)". These fundamental knowledge will help better utilize the chronic atrioventricular block monkeys as an in vivo proarrhythmia model for detecting drug-induced TdP.